The duration of alarm- and territorial defence calls alters receiver response in Eurasian magpies - Miriam Kuspiel; Arnout Lindeman; Marc Naguib; Sjouke A. Kingma (Animal Cognition)
Abstract Animals use vocal signals to provide information across a wide range of contexts. However, it is more complex to identify the information content when the same vocalizations are produced in different contexts, such as against predators and conspecific competitors. This raises the question whether information about the caller or context can be coded in relatively subtle variation within the call type and whether receivers respond differentially to such variation. Using playbacks of the general ‘chatter’ alarm call of Eurasian magpies (Pica pica), we tested whether or not territorial magpies respond differently to variation in call duration and rate. We show that magpies responded acoustically faster to chatters of longer duration, which may signal a greater motivation or urgency of territorial intruders. Alternatively, a delay in chatter response to shorter calls may reflect a period of hesitation and risk avoidance. Interestingly, magpies did not approach the loudspeaker more closely in response to longer calls and the total chatter response did not differ either. This suggests that after the short initial response, the persistence of the signal over time as well as visual information on the level or type of danger become essential for more differentiated response behaviours. Taken together, our results show that magpies perceive and respond differentially to variation in alarm call duration, suggesting that such variation encodes meaningful information.